Meaning The Philosophy Of Love In The Recent Era For A Spirit Of Learning In The Hindu Religion - I Ketut Subagiasta (IAHN-TP Palangka Raya, 2023)
The way to provide motivation to students is by providing a discussion regarding the philosophy of love in view of Hindu religious teachings according to the sacred literature of Hinduism. Enthusiasm for learning so that you concentrate towards successful learning. Love in Hindu philosophy is called heh, body, priti, and sneha. Students should be diligent in studying towards success, not prioritizing the study period as playing love. Come learn the philosophy of love in Sarasamuscaya, Bhagawadgita, Sokantara, Manwadharmaatra, Upanishad, Itiasa, and others.